2011
DOI: 10.7224/1537-2073-13.2.76
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden Among Informal Caregivers Assisting People with Multiple Sclerosis

Abstract: Multiple sclerosis (MS) burdens not only patients but also their informal or family caregivers. This study was conducted to identify characteristics of caregivers, caregiving, and MS patients receiving informal care that are associated with caregiving burden. Data were collected through a national survey of informal MS caregivers and analyzed using an ordered logistic regression model to identify factors associated with burden. Burden was found to be significantly greater among male caregivers than among femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 35 publications
(45 reference statements)
2
40
1
1
Order By: Relevance
“…MS is mostly diagnosed in early or middle adulthood, impacting family relations and the building and maintaining of a working career (Buhse, 2008). Life partners often become caregivers and provide daily assistance with personal care, homemaking, mobility, leisure activities and in coping with the disease (Buchanan et al, 2011;Carton et al, 2000). A recent study found that 58% of persons with MS report having at least one caregiver (Katsavos et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…MS is mostly diagnosed in early or middle adulthood, impacting family relations and the building and maintaining of a working career (Buhse, 2008). Life partners often become caregivers and provide daily assistance with personal care, homemaking, mobility, leisure activities and in coping with the disease (Buchanan et al, 2011;Carton et al, 2000). A recent study found that 58% of persons with MS report having at least one caregiver (Katsavos et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Research into positive aspects of caregiving for caregivers is scarce; the few studies that have been done report an increased sensitivity towards another person's needs and problems, companionship and a sense of fulfilment (Cohen et al, 2002;Knight et al, 1997). Other studies have found negative effects of caregiving on the caregiver's physical and mental health, social participation and financial situation (Buchanan et al, 2011;Buhse, 2008;Giordano et al, 2016;McKeown et al, 2003). Aspects of caregiving that were most negatively rated by spouses of persons with MS concerned worries about the future, the time burden involved and the fact that caregiving leads to more restrictions to life and less time available for the rest of the family (Knight et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Being in an informal caregiving role has been associated with negative outcomes such as depression, caregiver burden, and poor health-related quality of life in informal caregivers of a wide range of cohorts (i.e. traumatic brain injury (TBI), 6 dementia, 7 stroke, 8,9 multiple sclerosis (MS) 10 variables related to negative outcomes in the informal caregiving role, e.g. degree of disability of the care recipient, 11 amount of time spent providing care, 7 and mental health status of the caregiver, as being tied to caregiver outcomes.…”
Section: Introductionmentioning
confidence: 99%